Role of ADAM10 as a CD30 Sheddase in Classical Hodgkin Lymphoma - Hansen, Hinrich P.; Paes Leme, Adriana F.; Hallek, Michael (Frontiers in Immunology, 2020)
Cancer cells generally recruit and influence non-malignant immune cells to support the tumor growth. Classical Hodgkin lymphoma (cHL) is a good example because the affected lymphoid tissue contains only a few malignant Hodgkin and Reed-Sternberg (H-RS) cells, which are supported by a massive infiltrate of lymphocytes, fibroblasts, and innate immune cells. The transmembrane receptor CD30, which is selectively expressed on the H-RS cells, plays an important role, not only in cell stimulation and intercellular communication but also in tumor diagnosis and targeted tumor therapy. Different protein processing pathways influence its functionality. Depending on the conditions, the receptor is internalized or released. The release of CD30 occurs either as an intact molecule, embedded in the membrane of extracellular vesicles (EVs), or as a cleaved soluble ectodomain (sCD30). CD30 cleavage is predominantly catalyzed by ADAM10. The enzyme is catalytically active in cells as well as in EVs and gradually releases sCD30. Because the circulation contains no CD30+ donor cells, this mechanism explains that the cleaved ectodomain represents the predominant form of CD30 in the plasma of cHL patients. CD30 processing might influence the impact of CD30 antibody-drug conjugates, such as Brentuximab Vedotin (BV). Whereas, ADAM10-degraded CD30 impedes the BV efficacy, tumor-derived EVs load bystander cells with CD30 and generate new targets among supporter cells. This crossfire effect might contribute to the enormous clinical impact of BV, whereas the ADAM10-dependent cleavage to the mild systemic off-target effects of the treatment with BV.